1988
DOI: 10.1017/s0021859600082770
|View full text |Cite
|
Sign up to set email alerts
|

Water requirements and metabolism in Egyptian Barki and Rahmani sheep and Baladi goats during spring, summer and winter seasons

Abstract: Water requirements and metabolism were studied in eight each of Barki and Rahmani sheep and eight Baladi goats. The animals were individually housed in the shade in semi-open pens that were located in a non-desert area. The experiments were carried out during spring, summer and winter seasons, and each experiment lasted for 3 weeks during each season. After a preliminary period of 1 week, an 8-day period was then followed during which body weight, daily feed intake and daily drinking water were recorded. Recta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
4
11
0
Order By: Relevance
“…The cold-exposed sheep, on average, had higher (P < 0.05) Tr than animals in the warm environment (Table 1), consistent with a previous report by El-Nouty et al (1988). However, the initial Tr (day 0) was not affected by thermal environments.…”
Section: Rectal Temperaturesupporting
confidence: 90%
See 1 more Smart Citation
“…The cold-exposed sheep, on average, had higher (P < 0.05) Tr than animals in the warm environment (Table 1), consistent with a previous report by El-Nouty et al (1988). However, the initial Tr (day 0) was not affected by thermal environments.…”
Section: Rectal Temperaturesupporting
confidence: 90%
“…The water requirement is decreased in a cold environment (Winugroho et al 1987;El-Nouty et al 1988) and special mechanisms of water conservation have been used by herbivorous animals during periods of dehydration (Joyce and Blaxter 1964;Schmidt-Nielsen et al 1970). One such mechanism is that the degree of water absorption from the digestive tract appears to increase during dehydration (Goodall and Kay 1965;Maloiy et al 1978;Silanikove and Tadmor 1989).…”
Section: Heat Productionmentioning
confidence: 99%
“…In G, alterations in plasma volume were apparently in proportion to the thermoregulatory requirement. This response seems to be similar to those found in desertadapted goats (El Nouty et al, 1988;Silanikove, 2000a). We hypothesize that this is a strategy of G having smaller body size compared with S as a mechanism for coping with the high environmental temperature.…”
Section: Discussionsupporting
confidence: 81%
“…It appears that these two species of small ruminants have been well adapted to thrive in the harsh environment of Jeneponto, including the climate conditions as well as nutrient and water availability. This observation seems to conflict with numerous comparative studies that have suggested that goats are superior to sheep in thermoregulation, digestion, water balance and adaptive abilities (El Nouty et al, 1988;Silanikove, 1992;Silanikove, 2000a).…”
Section: Introductionmentioning
confidence: 69%
“…Sheep and goats share many anatomical and physiological characteristics, but some reports have indicated that differences with regard to water requirement and metabolism do exist between the two species. For instance, goats consume less water and have a lower water turnover rate than sheep, but with higher TBW content (Ghosh et al 1980;El-Hadi 1986;El-Nouty et al 1988). Awassi sheep and Aardi goats are known for their pronounced adaptation to harsh desert conditions, particularly limited water supply and heat stress (Alamer & Al-Hozab 2004;Alamer 2006).…”
mentioning
confidence: 99%